Borders and migrations within metropolitan areas: Reflections from Colonia Juarez’s case in Mexico City - Matossian, Brenda (2024)
Migrants cross not only international borders between states. In the cities where they remain they also face various types of “other” borders, both material and symbolic, that affect their experiences. The border configuration, linked to the presence of recent migrants -more specifically displaced people seeking refuge-, is investigated in a public space, the Giordano Bruno Park in Mexico City central area (Colonia Juárez), from a perspective that prioritizes qualitative techniques. The identified bordering processes are linked to both public migration policies and center-periphery tensions resulting from the capitalist logics that transform the metropolis. For migrants in search of their own preservation, grouping together becomes a strategy to survive, wait and spatialize their presence in the central areas of the city where these temporary refuge micro-spaces are sought.